Performance of finishing steers offered magnesium-mica in the feedlot ration - Coffey, K.P.; Brazle, F.K. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Forty-eight mixed-breed steers from two sources were used in a 141-day feedlot study to compare a control ration (C) with a ration containing magnesium-mica (MM; 9 lb/ton). No diet cattle source interactions were detected. Steer gain, efficiency, and cost of gain did not differ (P>.10) between diets. Marbling score tended (P<.10) to be greater and the percentage of cattle grading USDA Choice and net carcass value were greater (P<.05) for steers fed MM. Feeding MM in a feedlot ration may have a substantial economic impact on feedlot cattle.
Keywords: Beef; Magnesium-Mica; Feedlot cattle; Marbling score